Legal Politics of Land Rights Certification in The Indonesian Context: Between Agrarian Conflicts and Demands for Legal Certainty - Yasa, Putu Gede Arya Sumerta; Sudiarawan, Kadek Agus; Dwijayanthi, Putri Triari; Pranajaya, Made Dandy (International Journal of Criminology and Sociology, 2021)
This writing aims to analyze and identify the legal regulations and politics of registration (certification) of land rights in the context of Indonesian land law, particularly in Law No.5 of 1960 on Basic Agrarian Regulations (UUPA) amidst various agrarian conflicts and legal certainty documents over land rights that occur in Indonesia. This research will also seek to find comparisons that regulate and the politics of registering land rights in other countries. This is a normative legal research method with a statute approach and a comparative law approach. The results of the research show that the UUPA is a legal product in the field of agriculture that is unification for all Indonesians which is a mandate of the provisions of Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. Various agrarian conflicts that occur in Indonesia are caused by problems with land titles. Legal certainty through the certification of land rights is the answer to what agrarian law politics wants, considering that to create agrarian politics that makes people prosperous, protection of the rights inherent in land is needed. Through a clear foundation of rights will be able to increase economic value for landowners and improve the welfare of the Indonesian people at large. The regulation and politics of land registration law in several other countries such as Singapore, Malaysia, Mexico and Ethiopia also show the certification of land rights as an effort to provide protection and legal certainty for land that is used for community welfare.